Personalized Care and Treatment Compliance in Chronic Conditions - Teixeira, Fábio; Godinho, Catarina; Fernandes, Júlio Belo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
People who have chronic diseases spend a significant amount of time in self-management in out-of-hospital environments, in their homes and in their community settings. These patients have different disease statuses and management requirements, so providing personalized care is key.Personalized care is a collaborative process that should be used in chronic condition management in which patients, caregivers, and healthcare providers identify and discuss problems caused by or related to the patient's condition and then develop plans and goals to empower patients.Personalized care can improve aspects of physical health, mental health, and the ability to self-manage conditions. Thus, a personalized care approach could greatly benefit patients with chronic conditions.In this book, we have included 20 articles that expand the current knowledge on the personalized care approach to diagnosing and treating chronically ill patients.